Permanent education and expanded clinic: a new paradigm of care - Christine Teixeira Paz Azanki, Hayanne; Elias da Silva Gonçalves, Camila; Vitor Parreira Costa, João; da Costa Marques Vuolo, Valéria (Seven Editora, 2023)
Current health care requires conducts based on the proposal of comprehensive care, aimed at the subject and no longer for the disease. Aiming at comprehensive care through work in multiprofessional team, the current work proposes to relate the experience report of an expanded clinical practice proposed by the MT-Hemocentro and academics of the extension project "Sickle Cell Disease: pain that comes from the blood", with an bibliographic review on the subject, emphasizing the concepts of permanent and expanded clinical education, for the construction of a health intervention project that goes beyond the biomedical perspective towards new forms of care. DOI: https://doi.org/10.56238/tfisdwv1-070